Suporte social para idosos portadores de insuficiência cardíaca - Rezende, Luciana Krauss (2006)
With population aging, cardiovascular diseases have appeared in recent decades, in expressive proportions among the causes of morbidity and mortality. In Heart Failure there is an abnormality of cardiac function with consequent failure of the heart to pump blood to tissues, increasing the pressure of the heart (NEGRÃO et al., 2004). In order to assess the implications for lifestyle changes imposed by the disease, social support, defined by Cohen and Syme (1985), is included as tangible and emotional sources that are provided by some people to help others. Social support has been represented as comfort, assistance and information that the individual receives through formal and informal connections, individually or in groups (WALLSTON et al., 1983). Social support has been identified as a factor in determining the quality of life of the cardiac elderly. The aim of this research was to identify the existence of social support and the elderly's perception of the social support received among the elderly with heart failure, admitted to a hospital. In view of the above, we ask: Do our elderly patients receive social support to obtain a good quality of life? Is this social support satisfactory or unsatisfactory for these patients? The study was carried out at the Civil Foundation Casa de Misericórdia de Franca (Hospital do Coração Octávio Quércia), since the 20 participants had been hospitalized for some complication, in the institution mentioned. In our study, we observed that health professionals, bosses and / or coworkers are almost non-existent sources of support. How can we talk about advances in quality and health actions, if in our study, patients do not even recognize health professionals as a class that offers social support? On the contrary, patients are unaware of their actions and their benefits. Through the research it was possible to observe that solidarity from neighbors and friends is present, being a good indicator of support. It could be inferred that social cohesion is directly proportional to low income and education. Low education presupposes a high degree of conformity and satisfaction with the social support received. Finally, it was found that patients are satisfied or very satisfied with the social support received, these mostly carried out by family members followed by friends and neighbors. Only 10% of patients referred to health professionals. As for the patient's perception of social support, it was clear that he is understood as a synonym for family help and friends and neighbors.